Are campus police 'real' police? Students' perceptions of campus versus municipal police. (June 2021) - Allen, Andrea
Campus police (CP) actively enforce across US universities. Yet the public questions whether they are 'real' police, like municipal police (MP). Research finds students perceive CP and MP differently, generally holding the former in lower regard. However, little is known about exactly how students view CP as different from and similar to MP. This article addresses that gap by analyzing qualitative data from 73 university students. Participants perceive CP and MP as varying in training, powers, resources, sanction severity, and danger. The article concludes by discussing broader implications, including how comparing CP to MP can improve research, theory, and policing.